Differences in extracellular fluid volume between acute heart failure patients with and without high systolic blood pressure. (13th July 2022) - Namba, Yusuke; Yunoki, Kei; Nakamura, Kazufumi; Ejiri, Kentaro; Oka, Takefumi; Ito, Hiroshi
Abstract: Aims: Some reports have suggested that hypertensive acute heart failure (AHF) is caused by intravascular congestion, not interstitial congestion. We evaluated the differences in extracellular fluid volume assessed by bioelectrical impedance analysis (BIA) between AHF patients with and without high systolic blood pressure (sBP). Methods: This prospective single‐centre study (UMIN000030266) included 178 patients hospitalized due to AHF between September 2017 and August 2018. We calculated extracellular water (ECW), intracellular water (ICW), total body water (TBW), and ECW‐to‐TBW ratio (oedema index: EI) by BIA and evaluated conventional parameters as follows: weight, N ‐terminal pro brain natriuretic peptide values, and echocardiography parameters on admission and before discharge. One‐year outcomes included all‐cause death and re‐admission due to heart failure. We compared patients with sBP > 140 mmHg on admission [clinical scenario 1 (CS1) group] and with sBP of ≤140 mmHg on admission (non‐CS1 group). Results: The mean age of the patients was 79.5 ± 11.1 years, and 48.9% of the patients were female. EI on admission of 83 patients in the CS1 group was lower than that of 95 patients in the non‐CS1 group. The change in EI from admission to before discharge was no significant in the CS1 group but was significant in the non‐CS1 group. Comparing the changes from admission to before discharge between the CS1 and the non‐CS1 group, delta ECW, delta ICW, delta TBW, and delta EI of the CS1 group were significantly smaller than those of the non‐CS1 group. During the 1‐year follow‐up period after discharge of the 178 patients, the numbers of deaths and re‐admissions due to acute HF were 26 (15%) and 49 (28%), respectively. Patients with high EI before discharge [>0.408 (median)] had significantly more cardiac events than patients with low EI [hazard ratio (HR): 2.15, 95% confidence interval (CI): 1.30–3.55]. Cox regression analysis revealed that higher EI as a continuous variable was significantly associated with worse outcome in non‐CS1 group (HR: 1.46, 95% CI: 1.13–1.87), but not significantly associated with worse outcome in CS1 group (HR: 1.29, 95% CI: 0.98–1.69). Conclusions: EI on admission in patients with high sBP was not elevated, and changes in ECW, ICW, TBW, and EI in patients with high sBP were smaller than those in patients without high sBP. EI measured by BIA could distinguish AHF with interstitial or intravascular congestion.